Pengaruh Pengembangan Karir Terhadap Prestasi Kerja Pegawai Kantor Kecamatan Lenteng Kabupaten Sumenep yang Dimediasi Oleh Motivasi - Woro Utari; Mei Indrawati; Subhan Nofemri (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2024)
Subhan Nofemri, 2024. The Effect of Career Development on Work Achievement of Lenteng District Office Employees of Sumenep Regency Mediated by Motivation. Postgraduate Program at Wijaya Putra University Surabaya. This type of research uses explanatory research, the research approach uses a quantitative approach. The research sample was 42 respondents. The objectives of this study are 1) To prove and analyze the direct effect of career development on the work performance of employees of Lenteng District Sumenep Regency. 2) To prove and analyze the direct influence of career development on the motivation of Lenteng District Sumenep Regency. 3) To prove and analyze the direct effect of motivation on the work performance of employees of Lenteng District Sumenep Regency. 4) To prove and analyze the indirect effect of career development on the work performance of employees of Lenteng District Sumenep mediated by motivation. The results showed that: 1) Career development has no significant positive effect on employee performance at the Lenteng District Office, Sumenep Regency with an original sample value of 0.056. 2) Career Development has a significant positive effect on motivation at the Lenteng District Office, Sumenep Regency with an original sample value of 0.504. 3) Motivation has a significant positive effect on employee performance at the Lenteng District Office, Sumenep Regency with an original sample value of 0.333. 4) Career development has a significant positive effect on employee performance at the Lenteng District Office, Sumenep Regency which is mediated by motivation with an original sample value of 0.168.